2009
DOI: 10.1111/j.1523-1739.2009.01186.x
|View full text |Cite
|
Sign up to set email alerts
|

A Genomewide Assessment of Inbreeding Depression: Gene Number, Function, and Mode of Action

Abstract: Although the genetic basis of inbreeding depression is still being debated, most fitness effects are thought to be the result of increased homozygosity for recessive or partially recessive deleterious alleles rather than the loss of overdominant genes. It is unknown how many loci are associated with inbreeding depression, the genes or gene pathways involved, or their mode of action. To uncover genes associated with variation in fitness following inbreeding, we generated a set of inbred lines of Drosophila mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 53 publications
5
85
0
Order By: Relevance
“…In addition, molecular functional characterization of inbreeding-related phenomena may contribute to resolve the long-standing debate about the relative contributions of major genes to inbreeding depression. Recent evidence suggests that inbreeding depression is caused by a few major genes that in turn affect many other genes (Ayroles et al, 2009). Analyses of temperature-sensitive mutations are of relevance in relation to predicting the effect of global warming, besides also being important in relation to inbreeding by environment interactions (Parmesan and Yohe, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, molecular functional characterization of inbreeding-related phenomena may contribute to resolve the long-standing debate about the relative contributions of major genes to inbreeding depression. Recent evidence suggests that inbreeding depression is caused by a few major genes that in turn affect many other genes (Ayroles et al, 2009). Analyses of temperature-sensitive mutations are of relevance in relation to predicting the effect of global warming, besides also being important in relation to inbreeding by environment interactions (Parmesan and Yohe, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the genetic basis of inbreeding depression is, therefore, crucial for evaluating the evolutionary consequences of inbreeding. Recent evidence has shown that a large amount of inbreeding depression is caused by complex epistatic interactions between genes (Ayroles et al, 2009). This indicates that inbreeding depression is caused by a few deleterious genes with major effect that, in turn, affect a large proportion of the rest of the genome (Ayroles et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes being differentially expressed between inbred and outbred lines have been shown to include an overrepresentation of those associated with metabolism, stress and defense suggesting that inbreeding induces some of the same responses as environmental stress (Kristensen et al 2002;Pedersen et al 2005;Ayroles et al 2009;Paige 2010). It has been suggested that the deleterious effects of inbreeding could, at least to some extent, be ameliorated by a set of genes that respond to inbreeding (Vermeulen et al 2008).…”
Section: Inbreeding Effects On Molecular Phenotypesmentioning
confidence: 99%
“…Both gene expression and metabolite data indicate that fundamental metabolic processes are changed or modified by inbreeding (Kristensen et al , 2006Pedersen et al 2008;Ayroles et al 2009). Whether good quality individuals have higher or lower rate of metabolism is however still an unresolved question (Hawkins and Day 1999;Konarzewski and Diamond 1995;Reinhold 1999;Nilsson 2002;Rantala and Roff 2006;Johnston et al 2007;Ketola and Kotiaho 2009a, b;Mikkelsen et al 2010).…”
Section: Inbreeding Affects Metabolic Processesmentioning
confidence: 99%